Understanding Electrical Under- and Overshoots in Proton Exchange Membrane Water Electrolysis Cells. Issue 15 (1st January 2019) - Immerz, C.; Bensmann, B.; Trinke, P.; Suermann, M.; Hanke-Rauschenbach, R.
Abstract : Ability of dynamic operation seems to be an important feature of proton exchange membrane water electrolyzers (PEMWE) to become a relevant part of the future energy system. However, only few fundamental analyzes of the dynamic behavior on short time scales are available in the literature. Therefore, this contribution aims to give insights into the most fundamental transient behavior of a PEMWE cell by an experimental analysis on the laboratory scale and a model based description of the ongoing phenomena. Experimental voltage and current controlled load step are carried out and analyzed by methods adapted from fuel cell characterization. The experimental analysis revealed that load steps are a combination of an instantaneous characteristic followed by dynamics of higher order dependent on activation, mass transfer and temperature effects. Potentiostatic downward steps to very low cell voltages can lead to current density reversal phenomena with highly negative peak current densities. By means of a simple prototype model analysis, these reversal processes are analyzed and the consequences of the phenomena are estimated. The simulation results indicate that a reversal of the cell current density can be attributed to a change of capacitive rather than faradaic currents, meaning that internal electrolysis processes are not involved.